Dampak Perubahan Iklim Terhadap Pola Curah Hujan, Intensitas, dan Durasi Hujan di Distrik Jayapura Utara Berdasarkan Data Satelit GSMaP - Nurul Puspitasari; Janviter Manalu; Johnson Siallagan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Global climate change has caused changes in rainfall patterns in various regions, including North Jayapura District, Papua Province. This study aims to analyze changes in rainfall characteristics in the region over the past two decades (2004–2023) using GSMaP satellite data. The analysis was carried out on the average monthly rainfall, annual rainfall, decadal trends, hourly rainfall intensity frequency, and daily rainfall duration. The results showed a decrease in annual rainfall accumulation in the 2014–2023 decades compared to the previous decade (2004–2013), with a difference of around 5,000 mm. The seasonal rainfall pattern still shows concentration in January to March, but with a significant decrease in these wet months. In addition, there was an increase in the frequency of short-duration rain (<1 hour) and moderate to very heavy rain, although the frequency was still relatively small. The high variability of annual rainfall also indicates an increasingly large climate. These findings indicate that North Jayapura District faces the risk of increasing extreme rainfall events and decreasing water availability in the long term. Therefore, adaptation efforts are needed through improving early warning systems, conservation of air catchment areas, and integration of satellite data and field observations in air resource management planning.